Balancing the use of first and second serves - Pollard, G. (Medicine and Science in Tennis, 2008)
Originally the service in tennis was designed to start a rally and the server was given two opportunities, a first and second service, to put the ball into play. Gradually the service became stronger and more powerful and aided with modern powerful rackets many serves are aces or unplayable serves. This has lead to many sets in men`s tennis, especially men`s doubles, simply "going-with-service" until resolved by a tie-break. Although the set is close, service is generally held throughout by both players and the only real interest is in the tiebreak. Rather than limit the power of rackets, which could be legally challenging, this paper considers an alternative of balancing the use of first and second serves that still maintains an advantage for the server, but less than that currently enjoyed. This would make the game more exciting. In this paper five broad alternatives to the structure of a single game of tennis have been considered: 1. the present rule of two service opportunities on every point. 2. two service opportunities on up to six points in every game. It is assumed that the six occasions when the server has two service opportunities to put the ball into play, are the first six points in the game. Indeed, it has been shown that the first six points in a game would be the optimal selection for the server to use the six opportunities for two serves. Further, it would be much simpler for the umpire`s record-keeping to fix on these first six points rather than to allow the six points to be selected at various times by the server. Several aspects/complications of this alternative of allowing the server to choose when to take the two opportunities on a point (rather than just one) are discussed in the paper by Pollard and Pollard. 3. two service opportunities on only four points in every game. Correspondingly to (b) above, it is assumed that the four occasions when the server has two opportunities to put the ball into play, are the first four points in the game. As above, this rule would constitute an optimal strategy for the server with four points with two opportunities (rather than one) in a game. Also, this is a simple rule for the umpire to administer. 4. two service opportunities on only two points in every game. Correspondingly to (b) and (c) above, it is assumed that the two occasions when the server has the two opportunities to put the ball into play are the first two points in the game. As above, this rule is an optimal one for the server, and a simple one for the umpire. 5. only one service opportunity on all points in the game.